Diurnal variation in salivary cortisol across age classes in Ache Amerindian males of Paraguay. Issue 3 (18th October 2014) - Amir, Dorsa; Ellison, Peter T.; Hill, Kim R.; Bribiescas, Richard G.
<x xml:space="preserve">Abstract</x> Objectives Cortisol levels exhibit a diurnal rhythm in healthy men, with peaks in the morning and troughs in the evening. Throughout age, however, this rhythm tends to flatten. This diurnal flattening has been demonstrated in a majority of industrialized populations, although the results have not been unanimous. Regardless, little attention has been paid to nonindustrialized, foraging populations such as the Ache Amerindians of Paraguay. As testosterone levels had previously been shown to diminish with age in this population (Bribiescas and Hill [2010]: Am J Hum Biol 22: 216–220), we hypothesized that cortisol levels would behave similarly, flattening in rhythmicity over age. Methods We examined morning and evening salivary cortisol samples in Ache Amerindian men in association with age (n = 40, age range 20–64 years). Results Men in the first age class (<20–29 years) exhibited significantly different morning (AM) and evening (PM) values as did men in the second age class (30–39 years). However, men in the third and fourth age classes (40–49 years, and >50 years, respectively) did not exhibit a significant difference between AM and PM values. Conclusion Ache Amerindian men exhibit a flattening of the diurnal rhythm across age classes. Our results were able to capture both within‐ and between‐individual variations in cortisol levels, and reflected age‐related contrasts in daily cortisol fluctuations. The flattening of the diurnal rhythm with age among the Ache may reflect a common and shared aspect of male senescence across ecological contexts and lifestyles. Am. J. Hum. Biol. 27:344–348, 2015. © 2014 Wiley Periodicals, Inc.